Preventing the Criminalisation of Children Who Have Been Victims of Group-Based Sexual Exploitation Involving Grooming Tactics—Understanding Child Sexual Exploitation as Enslavement. (October 2019) - Arthur, Raymond; Down, Lisa
Recently the United Kingdom has been beset by a moral panic concerning gangs grooming girls for sexual exploitation. This moral panic derived from a number of well-publicised cases, the most infamous of which took place in Rochdale, Greater Manchester. Grooming children has been criminalised by section 15 of the Sexual Offences Act 2003. Adult groomers face up to two years in prison and being automatically placed on the sex offenders register. The Act is intended to protect children from abuse and exploitation. However child victims who have been abused by gangs and coerced into offending may still be liable for prosecution for any offending they have engaged in. Fear of being prosecuted may stop victims coming forward and prevent survivors from moving on with their lives. Such children are often perceived as having made a choice and criminalised. The Modern Slavery Act 2015 was designed to combat modern slavery. Recognising child sexual exploitation as a form of slavery, could lead to victims being protected rather than criminalised themselves for these offences. This article will examine how the law can be reformulated to ensure protection of children from sexual exploitation and also ensuring children are not charged for committing crimes whilst being groomed or coerced. The article will consider the limitation of the statutory defence available under section 45 of the Modern Slavery Act 2015.